ADVANCES IN THE USE OF STEM CELLS THERAPY IN VETERINARY CLINICAL PRACTICE - Z. A. Bhutta; M. F. A. Kulyar; A. Kanwal; W. Yao; R. Ahmed; S. Shabbir; M. Asif; S. Nawaz; M. Ali; M. Shoaib; A. S. Rukh; H. J. Arshad; et al. (Journal of Animal and Plant Sciences, 2022)
Stem cells are self-organized, unspecialized cells which are produced from various types of cells in all tissues of the body. They can be derived through a proper methodology from embryos, fetus and adults. Stem cells can divide into specific cell types, such as nerves or muscles. These cells are a source of information about cell differentiation processes and tissue homeostasis, but they are also one of the main biological tools for treating degenerative diseases. In the past 20 years, researchers have paid great attention to stem cell biology. Therefore, an understanding of its characteristics has greatly enhanced regarding to its therapeutic potential in all aspects in past few years. Role of stem cells is important for veterinary medicine in various ways. Several stem cell treatments for animals are currently being developed, such as treatment of equine tendinopathies disease through mesenchymal stem cells. In addition, animal models are widely being used to study the properties of stem cells and their potential in human medicine. These cells are now being artificially grown and transformed into special types of cell cultures that are compatible with cells from different tissues. This paper summarizes the current knowledge of stem cells potential in veterinary medicine.
Keywords: animal; regenerative medicine; stem cell therapy; stem cells; veterinary